History's legacy: Why future progress in ecology demands a view of the past - James A. Estes; Geerat J. Vermeij (Ecology, 2022)
History has profoundly affected the composition, distribution, and abundances of species in contemporary ecosystems. A full understanding of how ecosystems work and change must therefore take history into account. We offer four well‐studied examples illustrating how a knowledge of history has strengthened interpretations of modern systems: the development of molluscan antipredatory defenses in relation to shell‐breaking predators; the North Pacific kelp ecosystem with sea otters, smaller predators, sea urchins, and large herbivores; estuarine ecosystems affected by the decline in oysters and other suspension feeders; and the legacy of extinct large herbivores and frugivores in tropical American forests. Many current ecological problems would greatly benefit from a historical perspective. We highlight four of these: soil depletion and tree stunting in forests related to the disappearance of large consumers; the spread of anoxic dead zones in the ocean, which we argue could be mitigated by restoring predator and suspension‐feeding guilds; ocean acidification, which would be alleviated by more nutrient recycling by consumers in the aerobic ecosystem; and the relation between species diversity and keystone predators, a foundational concept that is complicated by simplified trophic relationships in modern ecosystems.

Impacts of deep‐sea mining on microbial ecosystem services - Beth N. Orcutt; James A. Bradley; William J. Brazelton; Emily R. Estes; Jacqueline M. Goordial; Julie A. Huber; Rose M. Jones; Nagissa Mahmoudi; Jeffrey J. Marlow; Sheryl Murdock; Maria Pachiadaki (Limnology and Oceanography, 2020)
Interest in extracting mineral resources from the seafloor through deep‐sea mining has accelerated in the past decade, driven by consumer demand for various metals like zinc, cobalt, and rare earth elements. While there are ongoing studies evaluating potential environmental impacts of deep‐sea mining activities, these focus primarily on impacts to animal biodiversity. The microscopic spectrum of seafloor life and the services that this life provides in the deep sea are rarely considered explicitly. In April 2018, scientists met to define the microbial ecosystem services that should be considered when assessing potential impacts of deep‐sea mining, and to provide recommendations for how to evaluate and safeguard these services. Here, we indicate that the potential impacts of mining on microbial ecosystem services in the deep sea vary substantially, from minimal expected impact to loss of services that cannot be remedied by protected area offsets. For example, we (1) describe potential major losses of microbial ecosystem services at active hydrothermal vent habitats impacted by mining, (2) speculate that there could be major ecosystem service degradation at inactive massive sulfide deposits without extensive mitigation efforts, (3) suggest minor impacts to carbon sequestration within manganese nodule fields coupled with potentially important impacts to primary production capacity, and (4) surmise that assessment of impacts to microbial ecosystem services at seamounts with ferromanganese crusts is too poorly understood to be definitive. We conclude by recommending that baseline assessments of microbial diversity, biomass, and, importantly, biogeochemical function need to be considered in environmental impact assessments of deep‐sea mining.

Size, growth, and density data for shallow‐water sea urchins from Mexico to the Aleutian Islands, Alaska, 1956–2016 - Thomas A. Ebert; Louis M. Barr; James L. Bodkin; Dirk Burcham; Dominique Bureau; Henry S. Carson; Nancy L. Caruso; Jennifer E. Caselle; Jeremy T. Claisse; Sabrina Clemente; Kathryn Davis; Paul M. Detwiler; et al. (Ecology, 2018)
Size, growth, and density have been studied for North American Pacific coast sea urchins Strongylocentrotus purpuratus , S. droebachiensis, S. polyacanthus , Mesocentrotus (Strongylocentrotus) franciscanus , Lytechinus pictus , Centrostephanus coronatus , and Arbacia stellata by various workers at diverse sites and for varying lengths of time from 1956 to present. Numerous peer‐reviewed publications have used some of these data but some data have appeared only in graduate theses or the gray literature. There also are data that have never appeared outside original data sheets. Motivation for studies has included fisheries management and environmental monitoring of sewer and power plant outfalls as well as changes associated with disease epidemics. Studies also have focused on kelp restoration, community effects of sea otters, basic sea urchin biology, and monitoring. The data sets presented here are a historical record of size, density, and growth for a common group of marine invertebrates in intertidal and nearshore environments that can be used to test hypotheses concerning future changes associated with fisheries practices, shifts of predator distributions, climate and ecosystem changes, and ocean acidification along the Pacific Coast of North America and islands of the north Pacific. No copyright restrictions apply. Please credit this paper when using the data.

A keystone ecologist: Robert Treat Paine, 1933–2016 - James A. Estes; Paul K. Dayton; Peter Kareiva; Simon A. Levin; Jane Lubchenco; Bruce A. Menge; Stephen R. Palumbi; Mary E. Power; John Terborgh (Ecology, 2016)
Robert T. Paine, who passed away on 13 June 2016, is among the most influential people in the history of ecology. Paine was an experimentalist, a theoretician, a practitioner, and proponent of the “ecology of place,” and a deep believer in the importance of natural history to ecological understanding. His scientific legacy grew from the discovery of a link between top‐down forcing and species diversity, a breakthrough that led to the ideas of both keystone species and trophic cascades, and to our early understanding of the mosaic nature of biological communities, causes of zonation across physical gradients, and the intermediate‐disturbance hypothesis of species diversity. Paine's influence as a mentor was equally important to the growth of ecological thinking, natural resource conservation, and policy. He served ecology as an Ecological Society of America president, an editor of the Society's journals, a member of and contributor to the National Academy of Sciences and the National Research Council, and an in‐demand advisor to various state and federal agencies. Paine's broad interests, enthusiasm, charisma, and humor deeply affected our lives and the lives of so many others.

The cost of reproduction: differential resource specialization in female and male California sea otters - Emma A. Elliott Smith; Seth D. Newsome; James A. Estes; M. Tim Tinker (Oecologia, 2015)

Animating the Carbon Cycle - Oswald J. Schmitz; Peter A. Raymond; James A. Estes; Werner A. Kurz; Gordon W. Holtgrieve; Mark E. Ritchie; Daniel E. Schindler; Amanda C. Spivak; Rod W. Wilson; Mark A. Bradford; Villy Christensen; Linda Deegan; et al. (Ecosystems, 2014)

Biological interactions maintain the boundaries between kelp forests and urchin barrens in the Aleutian Archipelago - Brenda Konar; Matthew S. Edwards; James A. Estes (Hydrobiologia, 2014)

A multi‐decade time series of kelp forest community structure at San Nicolas Island, California (USA) - Michael C. Kenner; James A. Estes; M. Tim Tinker; James L. Bodkin; Robert K. Cowen; Christopher Harrold; Brian B. Hatfield; Mark Novak; Andrew Rassweiler; Daniel C. Reed (Ecology, 2013)
San Nicolas Island is surrounded by broad areas of shallow subtidal habitat, characterized by dynamic kelp forest communities that undergo dramatic and abrupt shifts in community composition. Although these reefs are fished, the physical isolation of the island means that they receive less impact from human activities than most reefs in Southern California, making San Nicolas an ideal place to evaluate alternative theories about the dynamics of these communities. Here we present monitoring data from seven sampling stations surrounding the island, including data on fish, invertebrate, and algal abundance. These data are unusual among subtidal monitoring data sets in that they combine relatively frequent sampling (twice per year) with an exceptionally long time series (since 1980). Other outstanding qualities of the data set are the high taxonomic resolution captured and the monitoring of permanent quadrats and swaths where the history of the community structure at specific locations has been recorded through time. Finally, the data span a period that includes two of the strongest ENSO events on record, a major shift in the Pacific decadal oscillation, and the reintroduction of sea otters to the island in 1987 after at least 150 years of absence. These events provide opportunities to evaluate the effects of bottom‐up forcing, top‐down control, and physical disturbance on shallow rocky reef communities.

Interactions among sea otters, sea stars, and suspension-feeding invertebrates in the western Aleutian archipelago - Kenneth Vicknair; James A. Estes (Marine Biology, 2012)

Structure and mechanism of diet specialisation: testing models of individual variation in resource use with sea otters - M. Tim Tinker; Paulo R. Guimarães; Mark Novak; Flavia Maria Darcie Marquitti; James L. Bodkin; Michelle Staedler; Gena Bentall; James A. Estes (Ecology Letters, 2012)
Ecology Letters (2012) 15 : 475–483 Abstract Studies of consumer‐resource interactions suggest that individual diet specialisation is empirically widespread and theoretically important to the organisation and dynamics of populations and communities. We used weighted networks to analyze the resource use by sea otters, testing three alternative models for how individual diet specialisation may arise. As expected, individual specialisation was absent when otter density was low, but increased at high‐otter density. A high‐density emergence of nested resource‐use networks was consistent with the model assuming individuals share preference ranks. However, a density‐dependent emergence of a non‐nested modular network for ‘core’ resources was more consistent with the ‘competitive refuge’ model. Individuals from different diet modules showed predictable variation in rank‐order prey preferences and handling times of core resources, further supporting the competitive refuge model. Our findings support a hierarchical organisation of diet specialisation and suggest individual use of core and marginal resources may be driven by different selective pressures.

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Using Ecological Function to Develop Recovery Criteria for Depleted Species: Sea Otters and Kelp Forests in the Aleutian Archipelago - JAMES A. ESTES; M. TIM TINKER; JAMES L. BODKIN (Conservation Biology, 2010)
Recovery criteria for depleted species or populations normally are based on demographic measures, the goal being to maintain enough individuals over a sufficiently large area to assure a socially tolerable risk of future extinction. Such demographically based recovery criteria may be insufficient to restore the functional roles of strongly interacting species. We explored the idea of developing a recovery criterion for sea otters (Enhydra lutris) in the Aleutian archipelago on the basis of their keystone role in kelp forest ecosystems. We surveyed sea otters and rocky reef habitats at 34 island‐time combinations. The system nearly always existed in either a kelp‐dominated or deforested phase state, which was predictable from sea otter density. We used a resampling analysis of these data to show that the phase state at any particular island can be determined at 95% probability of correct classification with information from as few as six sites. When sea otter population status (and thus the phase state of the kelp forest) was allowed to vary randomly among islands, just 15 islands had to be sampled to estimate the true proportion that were kelp dominated (within 10%) with 90% confidence. We conclude that kelp forest phase state is a more appropriate, sensitive, and cost‐effective measure of sea otter recovery than the more traditional demographically based metrics, and we suggest that similar approaches have broad potential utility in establishing recovery criteria for depleted populations of other functionally important species .

Using stable isotopes to investigate individual diet specialization in California sea otters ( Enhydra lutris nereis ) - Seth D. Newsome; M. Tim Tinker; Daniel H. Monson; Olav T. Oftedal; Katherine Ralls; Michelle M. Staedler; Marilyn L. Fogel; James A. Estes (Ecology, 2009)
Differences in diet composition among conspecifics (dietary specialization) have been documented across a broad range of taxonomic groups and habitats, and such variation at the individual level is increasingly recognized as an important component of diversity in trophic interactions. Accurate identification of individual dietary specialization, however, requires longitudinal dietary records that are labor‐intensive and cost‐prohibitive to obtain for many species. Here we explore the use of stable isotopes (δ 13 C and δ 15 N) as a promising technique for detecting and quantifying patterns of individual dietary specialization. Southern sea otters ( Enhydra lutris nereis ) offer a unique opportunity for testing this approach because (1) they consume a wide variety of prey that span multiple trophic levels, habitats, and ecologically defined functional groups; and (2) individual diet specialization can be validated with existing observational data. We analyzed the isotopic composition of sea otter vibrissae ( n = 31) in order to characterize inter‐ and intra‐individual variation in sea otter diets at Monterey Bay, California, USA. At the population level, sea otters showed substantial variation in both δ 13 C and δ 15 N values, occupying nearly all of the “isotopic space” created by the diversity of isotopic signatures of potential prey taxa. Most of the variation in sea otter vibrissae was accounted for by differences between individuals, with much less contributed by within‐individual variation. A majority of sea otters (∼80%) showed relatively little temporal variability in isotopic composition, suggesting that the proportional composition of most individuals' diets is relatively constant over time; a few individuals (∼20%) exhibited a high degree of intra‐vibrissa isotopic variability, suggesting seasonal shifts in diet composition. These results and our interpretation of them were supported by long‐term observational data on the diets of radio‐tagged sea otters from the same population ( n = 23). Our results demonstrate that stable isotopes can provide an efficient tool for measuring individual‐ and population‐level dietary breadth and may be useful for studying populations where longitudinal data on individuals would otherwise be impossible to acquire. This will be critical for examining the causes and consequences of dietary variation within and among consumer populations, thereby improving our understanding of these important ecological and evolutionary processes at the community level.

FROM THE EDITOR - James A. Estes (Marine Mammal Science, 2006)

Indirect food web interactions: sea otters and kelp forest fishes in the Aleutian archipelago - Shauna E. Reisewitz; James A. Estes; Charles A. Simenstad (Oecologia, 2006)

Ecological Effectiveness: Conservation Goals for Interactive Species - Michael E. Soulé; James A. Estes; Joel Berger; Carlos Martinez Del Rio (Conservation Biology, 2003)
The rarity or absence of highly interactive species leaves a functional void that can trigger linked changes leading to degraded or simplified ecosystems. A preliminary analysis indicates a relatively high frequency of such interactive species among endangered mammals. Rapid environmental change is likely to increase the interactivity of some species and reduce that of others over relatively short intervals. The current implementation of environmental policies and laws, such as the U.S. Endangered Species Act, generally ignores interspecific effects; recovery goals are autecological, short term, and numerically and spatially minimalistic. Moreover, by failing to account for interspecific interactions, recovery objectives are becoming indefensible in light of increasing knowledge from community ecology. Using the sea otter ( Enhydra lutris ) and wolf ( Canis lupus ) as examples, we argue that conservation plans should call for recovery or repatriation of such interactive species at ecologically effective densities in as many places as are currently realistic. It will be prudent and beneficial to estimate ecologically effective densities where there is disagreement among experts and interested parties about the desirability of restoring an interactive species to a particular region and to a particular density.

SEA OTTER MORTALITY FROM THE EXXON VALDEZ OIL SPILL: EVALUATION OF AN ESTNATB FROM BOAT‐BASED SURVEYS - DAVID L. GARSHELIS; JAMES A. ESTES (Marine Mammal Science, 1997)